Exposure to ergot alkaloids during gestation reduces fetal growth in sheep - Duckett, Susan K.; Andrae, John G.; Pratt, Scott L. (Frontiers in Chemistry, 2014)
Tall fescue [Lolium arundinaceum (Schreb.) Darbysh; Schedonorus phoenix (Scop.) Holub] is the primary cool season perennial grass in the eastern U.S. Most tall fescue contains an endophyte (Neotyphodium coenophialum), which produces ergot alkaloids that cause vasoconstriction and could restrict blood flow to the fetus in pregnant animals. The objective of this study was to examine fetal growth during maternal exposure to ergot alkaloids during gestation. Pregnant ewes (n = 16) were randomly assigned to one of two dietary treatments: 1) endophyte-infected (Neotyphodium coenophialum) tall fescue seed (E+; 0.8 ug of ergovaline /g diet DM) and 2) endophyte-free tall fescue seed (E-; 0.0 ug of ergovaline/g diet DM). Birth weight of lambs was reduced by 37% for E+ compared to E-. Organ and muscle weights were also lighter for E+ than E-. Exposure to ergot alkaloids in utero reduces fetal growth and muscle development.